Knowledge graph and emerging trends in oxidative stress research on hepatic ischemia-reperfusion injury: a bibliometric analysis (1995–2024) - Lei, Simeng; Fu, Yangkai; Zhang, Bo; Yang, Hanwen; Ji, Zhili (Frontiers in Pharmacology, 2025)
BackgroundHepatic ischemia-reperfusion injury (HIRI) is a common complication in surgical procedures such as liver transplantation and extensive hepatectomy, characterized by an ischemic or hypoxic phase followed by reperfusion. Oxidative stress, primarily resulting from an imbalance between the generation and clearance of reactive oxygen species (ROS), plays a pivotal role in HIRI pathogenesis and has garnered significant research attention.ObjectiveThis bibliometric analysis comprehensively reviews global research trends and priorities in the study of oxidative stress in HIRI from 1995 to 2024, providing valuable insights and guidance for future researchers.MethodsWe conducted a systematic bibliometric analysis of relevant publications indexed in the Web of Science Core Collection (1995-2024), employing specific search qualifiers. Analyses were performed using CiteSpace (version 6.2.R6) and VOSviewer (version 1.6.20).ResultsFinal analysis included 2,367 publications. Over the past three decades, annual publication numbers in this field have consistently risen. China, the United States, and Turkey emerged as the leading contributing countries. Wuhan University, Sun Yat-sen University, and Shanghai Jiao Tong University ranked as the top three institutions by publication volume. The Journal of Surgical Research published the most articles, followed by Transplantation Proceedings and Free Radical Biology and Medicine. Rosello Catafau Joan, Lee Sun Mee, and Ye Qifa were identified as the most prolific authors. High-frequency keywords included “oxidative stress”, “ischemia reperfusion injury”, and “liver”.ConclusionOur findings indicate a shift in research focus from elucidating fundamental mechanisms towards exploring therapeutic interventions and associated protective effects. Nanotechnology and epigenetic modifications represent promising future avenues for treating HIRI in the therapeutic domain.